Evaluation of the Safety and Effectiveness of Ultrasound-guided Internal Jugular Vein Catheterization in Critically Ill Patients - Sultana, Rumana; Khan, Moffijul Haque; Morshed, Md Mahabub; Asrafuzzaman, Mohammad (Bangladesh Critical Care Journal, 2024)
Background:Central venous catheterization is a frequently performed procedure in intensive care units (ICU) for diagnostic and therapeutic purpose. As an invasive procedure it carries some risk and should be performed with few attempts. Traditionally this procedure is performed blindly by considering body surface landmark, but this procedure can be done with the help of ultrasound machine as an alternative of landmark procedure. Objectives: Evaluation of the safety and effectiveness of USG-guided internal jugular vein(IJV) catheterization in critically ill patients. Methods: This prospective observational study was conducted in the ICU of Dhaka Medical College Hospital, from May 2017 to October 2018. Patients scheduled for central venous catheterization via the IJV were included based on selection criteria and randomly allocated into two groups of 50 patients each using card sampling. Group A received ultrasound-guided catheterization, while the landmark technique was used in Group B. Results: The analysis revealed that in the ultrasound group 49 out of 50 (98.0%) patients were successfully catheterized while the landmark method was successful in 45 out of 50 (90.0%) patients. Successful catheterization by first attempt was possible in 29 patients of group A, where as it was 5 in group B. The average number of attempts for successful catheterization in Group A was 1.7 (SD=0.2) and in the landmark group it was 2.8 (SD=0.1). On the average, 4.9 minutes (SD=1.3) were needed for catheterization in ultrasound group. The time was significantly increased in the landmark group 11.4 (SD=5.8). Total number of complication was 2 in Group A and it was 8 in Group B. After considered all the above parameter, by using four points safety and effectiveness rating scale, safety and effectiveness mean score was 10.3 for Group A and 8.2 for Group B. Conclusion: Two-dimensional ultrasound offers improved safety and quality when compared with an anatomical landmark technique for IJV catheterization. Bangladesh Crit Care J September 2024; 12 (2): 96-104